2002
DOI: 10.1084/jem.20021515
|View full text |Cite
|
Sign up to set email alerts
|

CD1-mediated γ/δ T Cell Maturation of Dendritic Cells

Abstract: Immature myeloid dendritic cells (DCs) express only low levels of major histocompatibility complex (MHC) class II but express high levels of CD1 a, b, and c antigen-presenting molecules at the cell surface. As Vδ1+ γ/δ T cells are the main tissue subset of γ/δ T cells and they are known to recognize CD1c in the absence of specific foreign antigen recognition, we examined the possible interaction of these T cells with immature DCs. We show that CD1-restricted γ/δ T cells can mediate the maturation of DCs. DC ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
155
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(167 citation statements)
references
References 33 publications
8
155
2
Order By: Relevance
“…Our results are in concordance with previous reports showing modulation of DC activity by cells restricted by monomorphic nonclassical MHC class I-like molecules (15,16). In addition, DNA microarray analysis of human iNKT activated with anti-CD3 Abs has been reported to show cytokine and chemokine expression profiles consistent with the recruitment and maturation of DC (49).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are in concordance with previous reports showing modulation of DC activity by cells restricted by monomorphic nonclassical MHC class I-like molecules (15,16). In addition, DNA microarray analysis of human iNKT activated with anti-CD3 Abs has been reported to show cytokine and chemokine expression profiles consistent with the recruitment and maturation of DC (49).…”
Section: Discussionsupporting
confidence: 82%
“…In support of this hypothesis, it has been shown in mice that stimulation of iNKT cells can enhance DC-based immunization strategies (14). Also, recent studies have shown that human NKT cell clones restricted to the group I CD1 molecules CD1a, CD1b, and CD1c, and ␥␦ T cells restricted by CD1c can directly induce maturation of cultured DC in vitro (15,16). Therefore, a range of CD1-restricted cells may be poised, together with direct microbial stimuli, to integrate innate immune responses with appropriate adaptive responses.…”
mentioning
confidence: 65%
“…The molecular nature of such factors is not known but Ruedl et al (12) and Muraille et al (8) have excluded CD28, CD40L, receptor activator of NF-B ligand, TNF, IL-1, IL-4, IL-6, IL-17, IFN␣␤, and IFN-␥. In contrast, human DC maturation induced by CD8 ϩ or ␥␦ T cells is largely mediated by IFN-␥ and/or TNF, respectively (13,38).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated CD1a, CD1b, CD1c and CD1d reactivity of human Vd1 + T cells [198][199][200][201][202][203] and CD1d-reactivity of human Vd3 + T cells [204]. Roles for CD1-restricted Vd1 + and Vd3 + T cells in the induction of adaptive immune responses are evident from studies that have shown that these cells can induce MHC and costimulatory receptor expression and cytokine production by DC, conferring upon DC the capacity to drive alloreactive T cell proliferation [204,205]. Additionally, one report described the ability of CD1-restricted Vd1 + T cells specific for pollen-derived phosphatidyl-ethanolamine to drive IgE production by B cells [200].…”
Section: Innate Regulation Of Adaptive Immune Responses: Vd2 + Versusmentioning
confidence: 99%